A social media program to increase adolescent seat belt use. Issue 5 (6th July 2017) - Drake, Stacy A.; Zhang, Ni; Applewhite, Courtney; Fowler, Katherine; Holcomb, John B.
Abstract: In response to motor vehicle crashes remaining the leading cause of death for teenagers in the United States, a nursing clinical group ( n  = 10) in conjunction with a local hospital injury prevention program created an educational campaign to bolster seat belt use. The nursing students created an Instagram account to serve as an educational tool to promote seat belt use among teenagers aged 14–19, and the program was presented at three high school health fairs. In all, 135 postings were made to the account over a 3‐month period. The number of likes posted by high school students was the unit of analysis. The most significant result ( p  = .01) was the difference between postings most liked (celebrities wearing seat belts) and least liked (postings made at the high school health fair), otherwise, differences among postings liked (humor postings, response requests, pictures of celebrities, factual data) were not significant. Instagram user engagement, measured in number of likes, is indicative that social media provides platforms to promote injury prevention efforts. Further research is needed to identify measurable elements of social media and to follow‐up on behavioral changes following participation.